Synthesis and characterization of a novel colorimetric and fluorometric probe “Turn-on” for the detection of Cu2+ of derivatives rhodamine - Segura, Camilo; Yáñez Osses, Osvaldo Andrés.; Galdámez, Antonio; Tapia, Victoria; Núñez, Marco T.; Osorio Román. Igor.; García, Camilo; García Beltrán, Olimpo. (Elsevier, 2023)
A new Rhodamine-based “Turn On” fluorescent probe (E)- 3′,6′-bis(diethylamino)-2-((2,5-dimethoxybenzylidene)amino)spiro[isoindoline-1,9′-xanthen]-3-one (WGB) was synthesized. Results show that WGB is selective for Cu2+ cations, forming a WGB-Cu2+ complex in a 2:1 stoichiometry, confirmed through density functional theory (DFT) electronic structure calculations and reactive molecular dynamics (MD) simulations. Theoretical calculations agreed with the experimental data. The detection limit of WGB-Cu+2 complex is 6.76 × 10-8 M. Preliminary studies employing epifluorescence microscopy demonstrate that Cu2+ can be imaged in neuroblastoma SH-SY5Y cells treated with WGB.
Keywords: Chemosensor; Colorimetric fluorescent dye - Cu2+ ions; Rhodamine derivate; Turn-On